STRUCTURE AND REQUIREMENTS FOR A UNIVERSAL TRAINING DEVICE FOR UNMANNED AIRCRAFT COMPLEXES - Druzhynin, Volodymyr; Matiychyk, Mykhailo; Rogozhyna, Nina; Fuzik, Mykhailo; Rybalchenko, Oleksandr (Proceedings of National Aviation University, 2021)
The problems of personnel training for the operation of unmanned aerial vehicles have been updated. The differences between the skills and abilities of personnel for manned and unmanned aircraft are highlighted. The widespread types of flight simulators are considered, their features are given. The basic schemes of application of linear and nonlinear mathematical models of formation (formalization) of knowledge, abilities and skills of the personnel taking into account absence / presence of updating of the information in the course of training are substantiated. The basic modes of operation of USL, the universal simulator for training are specified. Emphasis is placed on the fact that USL is a partial case of an automated training management system (ACS), and a block diagram of training with it is given. The tasks that can be solved on a universal simulator and the requirements for software and hardware, automated workplace, digital sound, general software, peripherals, data exchange, digital video, user interface and webbased automated instructions are discussed in detail. The functions and structure of the universal simulator for training unmanned aircraft complex are presented.